PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINKTALK WRITE (TTW) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI MIPA - Andini, Laura (Departemen Matematika, 2023)
One of the learning objectives that must be mastered in learning mathematics is understanding the concept. The reality on the ground found that the understanding of mathematical concepts in class XI MIPA SMA N 3 Pariaman was still low. One effort that could overcome this problem was to apply a cooperative learing model of the think talk write type in the mathemathics learning process. The purpose of study was to determine the development of students’ understanding of mathematics while studying with the cooperative learning model of the think talk write. The type of research in quasi-experimental with Non-equivalent Posttest Only Control Group Design. Based on the anlalysis of the data it can be concluded that the understanding of students who learn using the cooperative learning model type think talk write is better than the understanding of mathematical concepts of students who learn using conventional learning.Keywords¾ConceptuaI Understanding, Think Talk Write